The Implicit Associations Between Religious and Nonreligious Supernatural Constructs. Issue 2 (3rd April 2017) - Weeks, Matthew; Gilmore, Alex
ABSTRACT: The present studies furthered understanding of the implicit relationships between traditional religious (RS) and nonreligious supernatural (NRS) concepts. Moving beyond the study of explicit beliefs, we accounted for the distinctions within NRS concepts, applying recent developments in the understanding of the correspondence in beliefs in these phenomena.